2022
DOI: 10.1111/ced.15156
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an appropriate level of vitamin D supplementation in paediatric patients with recessive dystrophic epidermolysis bullosa

Abstract: Summary Background Paediatric patients with recessive dystrophic epidermolysis bullosa (RDEB) are at risk of vitamin D deficiency, owing to lack of sunlight from reduced mobility and having large areas of skin being covered with dressings, and to impaired nutritional intake and status. Aim To establish an appropriate level of vitamin D supplementation in paediatric patients with RDEB. Methods Patients with RDEB attending the EB tertiary multidisciplinary team clinic were enrolled. Serum levels of total 25(OH)D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Patients generally presented with low serum 25-hydroxyvitamin D (25(OH)D) levels. 3,7,8,16,17,20,24 Deficiencies of vitamin D were often present by the second year of life, despite recommended supplementation in RDEB and JEB. 7 Calcium levels were reported as normal after correction with albumin, 8,20 but calcium intake in children may be insufficient to maintain bone health.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients generally presented with low serum 25-hydroxyvitamin D (25(OH)D) levels. 3,7,8,16,17,20,24 Deficiencies of vitamin D were often present by the second year of life, despite recommended supplementation in RDEB and JEB. 7 Calcium levels were reported as normal after correction with albumin, 8,20 but calcium intake in children may be insufficient to maintain bone health.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Other than the demonstration of low 25(OH)D concentrations, 3,7,8,16,17,20,24 the pathophysiology of bone metabolism in EB. That said, one study found a significant correlation between IGF-1 and aBMD.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation